Changes of the vertical dimension after expansion using bonded acrylic splint expander a clinical study - Hasan, Abdul Kareem; Tizini, Mohammad; Haffaf, Radwan Aziz (Latakia University Journal -Medical Sciences Series, 2020)
Introduction: increasing of the vertical dimension is an undesired side effect of the palatal expansion. it had been assumed that the bonded acrylic splint expander may decrease the vertical changes subsequent to expansion which is important for patients with increased vertical dimension, it may be related to the supposed intrusive force caused by the posterior bite block of this design, this study aimed to evaluate the changes of the vertical dimension in mixed dentition patients; after using the bonded acrylic splint expander. Materials and methods: the sample consisted of 18 patients in the mixed dentition, aged 6-12 years and diagnosed with maxillary transvers deficiency without any indication for other intervention. They had been evaluated radiographically using lateral cephalometric image before treatment T1. the expander activated 1 turn per day until overcorrection of 2-3 mm was gained. Retention period was 6 months. The appliances were removed and the patients re-evaluated again T2. The vertical dimension was inspected using 4 different parameters. Results: The results of paired samples T.test indicated no statistically significant differences before and after treatment. Conclusion: rapid maxillary expansion using bonded acrylic splint expander did not alter Y axis, Bjork sum, UFH/LFH or Jarabak ratio in mixed dentition patients. مقدمة: من التأثيرات الجانبية غير المرغوبة للتوسيع الحنكي أنه يمكن أن يسبب زيادة البعد العمودي. يعتقد أن الموسعة ذات الجبيرة الإكريلية الملصقة تقلل من التغيرات العمودية التالية للتوسيع، الذي هو أمرٌ هام عند المرضى ممن لديهم زيادة في الارتفاع الوجهي. يعتقد أن ذلك يعود إلى القوى الغارزة المُفتَرضَة بتأثير رفع العضة الخلفي لتصميم الجبيرة الإكريلية هذا. هدفت هذه الدراسة إلى تقييم تغيرات البعد العمودي عند المرضى في مرحلة الإطباق المختلط؛ المعالجين باستخدام التوسيع الفكي السريع بالموسعة ذات الجبيرة الإكريلية الملصقة. المواد والطرق: تضمنت العينة 18 مريضاً في مرحلة الإطباق المختلط تراوحت أعمارهم بين 6-12 سنة مع عجزٍ معترضٍ في الفك العلوي؛ دون الحاجة لأي تداخل علاجي آخر. تم إجراء تقييم شعاعي باستخدام التصوير السيفالومتري الجانبي قبل العلاج T1. تم تنشيط الجهاز بمعدل مرة واحدة يومياً حتى الوصول إلى تصحيحٍ زائدٍ بمقدار 2-3 مم. كانت مدة التثبيت 6 أشهر. بعدها تم نزع الأجهزة وإجراء التقييم الشعاعي بعد العلاج T2. قُيم البعد العمودي باستخدام أربعة متغيرات مختلفة. النتائج: أشارت نتائج اختبار Paired samples T.test إلى عدم وجود فروق معتبرة لمتوسطات قيم البعد العمودي قبل العلاج وبعده. الاستنتاجات: لا يؤدي التوسيع الفكي العلوي السريع باستخدام الموسعة ذات الجبيرة الإكريلية الملصقة إلى أي زيادة معتبرة في محور Y ، نسبة جاراباك، مجموع بيورك أو نسبة UFHعند المرضى في مرحلة الإطباق المختلط.